CELIE’S CHARACTERISTIC IN ALICE WALKER’S THE COLOR PURPLE - Sutriani Sutriani (Humaniora Scientia, 2018)
This study is related to the characteristics and character development of the main character in Alice Walker’s The Color Purple, Celie. There are two objectives of the study namely, (1) to find out Celie’s characteristics, (2) to explain Ceie’scharacter development in the novel. It is a descriptive research with the novel The Color Purple as the main source of data. The data were collected through library study and internet browsing. This research made use of the theories of character, characterization, psychology, personality, and personality development. Moreover, sociological and psychological approaches were applied to analyze the data. The data analysis shows as follows: (1) Celie’s characteristics include weakness, patience, obedience, and lovability, (2) Celie’s character development causes Celie to be a cheerful, brave, and hard worker woman.